Downregulation of beclin 1 restores arsenite-induced impaired autophagic flux by improving the lysosomal function in cortex - Hongmei Zhou; Hong Ling; Yunlong Li; Xuejun Jiang; Shuqun Cheng; Golamaully Mohammad Zubeir; Yinyin Xia; Xia Qin; Jun Zhang; Zhen Zou; Chengzhi Chen (Ecotoxicology and Environmental Safety, 2022)
Arsenite is a toxic metalloid that causes various adverse effects in brain. However, the underlying mechanisms of arsenite-induced neurotoxicity remain poorly understood. In this study, both adult beclin 1+/+ and beclin 1+/- mice were employed to establish a model of chronic arsenite exposure by treating with arsenite via drinking water for 6 months. The results clearly demonstrated that exposure of arsenite profoundly caused damage to the cerebral cortex, induced autophagy and impaired autophagic flux in the cerebral cortex. Heterozygous disruption of beclin 1 in animals remarkably alleviated the neurotoxic effects of arsenite. To verify the results obtained in the animals, a permanent U251 cell line was used. After treating of cells with arsenite, similar phenomenon was also observed, showing the significant elevation in the expression levels of autophagy-related genes. Importantly, lysosomal dysfunction caused by arsenite was observed in vitro and in vivo. Either knockdown of beclin in cells or heterozygous disruption of beclin 1 in animals remarkably alleviated the lysosomal dysfunction induced by arsenite. These findings indicate that downregulation of beclin 1 could restore arsenite-induced impaired autophagic flux possibly through improving lysosomal function, and suggesting that regulation of autophagy via beclin 1 would be an alternative approach for the treatment of arsenite neurotoxicity.